The Effect of Passive Smoking during Pregnancy on the Central Nervous System Structure and Behaviour of the Offspring - Omar Abuzant; Waseem Khraim; Watheq Sharqia; Waleed Ajaj; Walid Basha (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
Exposure to tobacco smoke during pregnancy is considered a major preventable risk factor for morbidity and mortality of the mother and the foetus. This study aims to investigate the effect of passive smoking during pregnancy on the structural integrity of the central nervous system (CNS) of the offspring, and to assess their neurobehavioral functions including short term memory, anxiety and social interactions. For this 35 pregnant hamsters were divided into 5 groups, based upon the pregnancy trimesters they were exposed to smoke in (during the 1st trimester or the 2nd and 3rd trimesters together) as well as the duration of exposure (4 or 6 hours). The 35 pregnant hamsters produced 78 offspring, which were evaluated at age 8 weeks for memory function by T-maze test, anxiety using marble burying test and social behaviour by social dominance test. They were also examined by CT scan subsequently for gross structural abnormalities in the CNS. The results demonstrated that there is a significant correlation between exposure to passive smoking during the 1st trimester and the presence of short-term memory impairment (p= 0.047), as well as increasing anxiety level (p=0.024). Exposures during the 2nd and 3rd trimesters were also associated with short-term memory dysfunction, with no effect on anxiety level. CT reports showed lumbar canal stenosis in a significant number of offspring who were exposed to 6 hours of cigarette smoke during the 1st trimester of pregnancy. Our results conclude that passive smoking during pregnancy is dangerous to the CNS development of the foetus as was evident by its effect on the behaviour of the offspring and structural integrity of their CNS.